Contemporary and future distributions of cobia, Rachycentron canadum. Issue 8 (8th June 2020) - Crear, Daniel P.; Watkins, Brian E.; Saba, Vincent S.; Graves, John E.; Jensen, Douglas R.; Hobday, Alistair J.; Weng, Kevin C.
Abstract: Aim: Climate change has influenced the distribution and phenology of marine species, globally. However, knowledge of the impacts of climate change is lacking for many species that support valuable recreational fisheries. Cobia ( Rachycentron canadum ) are the target of an important recreational fishery along the U.S. east coast that is currently the subject of a management controversy regarding allocation and stock structure. Further, the current and probable future distributions of this migratory species are unclear, further complicating decision‐making. The objectives of this study are to better define the contemporary distribution of cobia along the U.S. east coast and to project potential shifts in distribution and phenology under future climate change scenarios. Location: Chesapeake Bay and the U.S. east coast. Methods: We developed a depth‐integrated habitat suitability model using archival tagging data from cobia that were caught and tagged in Chesapeake Bay during summer months and coupled those data with high‐resolution ocean models to project the contemporary and future distributions of cobia along U.S. east coast. Results: During the winter months, suitable cobia habitat currently occurs in offshore waters off North Carolina and further south, whereas during the summer months, suitable habitat occurs in waters from Florida to southern New England. In warmer years, the availability of suitable habitat increases in northern latitudes. Under continued climate change over the next 40–80 years, suitable habitat is projected to shift northward and decrease over the shelf. Main conclusions: Habitat distributions suggest cobia overwinter offshore and could inhabit waters further north during warmer months, into state jurisdictions that do not have strict management regulations for cobia. When waters are warmer, distributions are projected to shift poleward and seasonal migrations may begin earlier. These results can inform resource allocation discussions between fishery managers and resource users.